The Charnoly body : a novel biomarker of mitochondrial bioenergetics - Sharma, Sushil, Ph. D., D.M.R.I.T. (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
Diversified physicochemical injuries trigger Charnoly body (CB) formation as pleomorphic, electron-dense, multi-lamellar stacks of nonfunctional mitochondrial membranes in the most vulnerable cell. Free radicals induce downregulation of mitochondrial DNA, microRNA, AgNOR, and epigenetics to trigger CB molecular pathogenesis. CB is eliminated by energy (ATP)-driven lysosome-dependent charnolophagy as a basic molecular mechanism of intracellular detoxification to prevent acute and chronic diseases. Accumulation of CB at the junction of axon hillock and charnolosome (CS) at the synapses causes cognitive impairments; whereas, nonspecific induction of CB causes GIT stress, myelosuppression, alopecia, neurotoxicity, cardiotoxicity, and infertility in multidrug-resistant malignancies. Hence, stem cell-specific CB, charnolophagy, and CS agonists/antagonists are introduced as novelcharnolopharmacotherapeutics for the successful treatment of cardiovascular diseases, neurodegenerative diseases, infectious diseases, drug addiction, and cancer. Nanoparticles to improve drug delivery, CS exocytosis, and disease-specific spatiotemporal charnolosomics employing correlative and combinatorial bioinformatics boost mitochondrial bioenergetics through balanced diet, exercise, and antioxidants. The book will be of interest to medical scientists and practitioners.
Free radical-induced compromised mitochondrial bioenergetics triggers Charnoly body formation (free radical hypothesis of charnoly body formation; stages of intracellular toxification/detoxification; biomarkers of intracelular detoxification) -- Free radical-induced molecular pathophysiology of Charnoly body and charnolosome -- Charnoly body as a novel biomarker of cell injury -- Charnoly body as a novel biomarker of compromised mitochondrial bioenergetics (biomarkers of CMB; free radical-induced CB molecular pathogenesis) -- Antioxidants prevent Charnoly body formation, augment charnolophagy, and stabilize charnolosome to enhance mitochondrial bioenergetics and intracellular detoxification (therapeutic potential of antioxidants in response to different -- Stages of a free radical attack) -- Metallothioneins inhibit charnoly body formation and confer structural and functional stability to charnolosome (therapeutic potential of metallothioneins (MTS) as CB antagonists; therapeutic potential of (MTS) as charnolosome (CS) stabilizers) -- The Charnoly body : a novel biomarker of mitochondrial bioenergetics -- Clinical significance of Charnoly body as a biomarker of compromized mitochondrial bioenergetics in multidrug resistant diseases -- Development of novel charnolopharmacotherapeutics in pharmaceutical industry by flow cytometric analysis -- Charnoly body as a novel biomarker in nanomedicine (Charnoly body, charnolophagosome, and charnlosome as potential nanotheranostic biomarkers in evidence based personalized medicine) -- Clinical significance of mitochondrial bioenergetic and Charnoly body in evidence based personalized nanotheranostics -- Translational multimodality neuroimaging of Charnoly body, charnolophagy, and charnolosome for personalized theranostics of chronic MDR diseases -- Pet radiopharmaceuticals and surface plasmon resonance spectroscopy for Charnoly body and micro-RNA based personalized theranostics -- Therapeutic potential of stem cells from different biological sources as Charnoly body anagonists, charnolophagy agonists, and charnolosome stabilizers -- Charnolopharmacotherapeutics of chronic multidrug resistant diseases by metallothionein-induced hypoxia inducible factor-1 -- Clinical significance of disease-specific Charnoly body formation -- Charnoly body in fetal alcohol syndrome -- Charnoly body in nicotinism -- Charnoly body in ZIKV disease -- Charnoly body in malnutrition -- Charnoly body in drug addiction and other chronic multi-drug-resistant diseases (therapeutic potential of MTS) -- Charnoly body in cardiovascular diseases -- Charnoly body in stroke -- Charnoly body in traumatic brain injury -- Charnolopharmacotherapy of neurodegenerative and other diseases.
"A Science Publishers book."
OCLC-licensed vendor bibliographic record.
Keywords: Metallothionein; Biochemical markers; SCIENCE / Life Sciences / Biochemistry; MEDICAL / Biochemistry; SCIENCE / Life Sciences / Cytology; SCIENCE / Physics